The understanding and perception towards corporate social responsibility (CSR) program by Bachelor (Hons) In Public Relations student in UiTM Melaka Alor Gajah Campus / Nur Syahira Afiqah Mohd Fahmi - Mohd Fahmi, Nur Syahira Afiqah (Faculty of Communication and Media Studies, 2018)
Corporate Social Responsibility (CSR) is a corporation's social and environmental obligations to its constituencies and greater society. It's being used more frequently by constituencies to analyze and critique corporate behavior. It is important for PR practitioner understand on this matter. This research is to seek the student's understanding and perception towards CSR especially in Bachelor of Public Relations student because as we know, CSR is one of the important practice that PR practitioners need to understand. It will also focus on the relationship of the listed understanding aspect and perceptions towards the student's interest in CSR program. The Corporate Social Responsibility (CSR) is not a bizarre term in corporate sector but it still not define clearly what is the level of understanding and the perception in the university angle, especially Public Relations students in Universiti Teknologi Mara (UiTM) Melaka. There PR students are the target respondents. There are 90 students. The quantitative analysis is used to identify the student level of understanding and perception towards CSR program. A set of questionnaire has been distributed to the random students for the data collection. The related theory in this research is Cognitive Dissonance theory. The early assumption expect that the CSR exposure among the student is not good and still underdeveloped.